(untitled) (Fiep Bulletin - online, 2012)
This works aims to diagnose the learning performance of children with mental disabilityduring adapted physical education. A methodology of assessing the level of the learning process ofswimming motion was developed and tested for two years within two groups of children with mentaldisability. No essential difference was observed in the speed or quality of learning of the basicswimming movements, neither between girls and boys, nor between age groups. The assessmentmethodology has shown to be adequately able to help separate sportsmen into several performancegroups for subsequent swimming preparation.